KATA GANTI ORANG BAHASA INGGRIS DAN BAHASA KLABRA (Suatu Analisis Kontrastif) - MARAR, ESAU (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This skripsi is entitled "The Personal Pronoun of English and Klabra Language; â€œA Contrastive Analysisâ€. This study has the objective to identify, categorize and analyze the personal pronoun of English and Klabra language based on form, function and meaning. In addition to identifying and classifying the person pronouns of language, the study also aims to compare or contrast the similarities and differences between English and more particularlyÂ  personal pronouns of Klabra language which are based on the theory of Marcella Frank (1972:29). Â  There are two theories on personal pronouns used in this research, namely by Frank (1972: 29) and Bloomfield (1933). The English data were collected from English textbooks and some linguistic books, while the data about Klabra language were obtained from informants through telephone communications. Â  English is a member of the family of Germanic languages, derived directly from the Indo-European, whereas Klabra language is Austronesian language family. From the results of this study, it is found that the pronoun in English and Klabra language can be devided into the first personal pronoun, second and third. There are similarities and differences in the personal pronoun of English and Klabra language. There are several similarities in both languages, one of them is in the function as subject and object, and the two languages â€‹â€‹have equal placement in the sentence that is before the verb and after the noun. There are many differences in both languages, one of them is English has one form of the second personal pronoun called you both singular and plular, whereas Klabra language has two forms, they are nin for the singular second personal pronoun and nan for the plural second personal pronoun. Keywords:Â Â Personal Pronouns, Contrastive Analysis: English, Klabra Language, Function and Meaning.